Effect of quadrat shapes on measurement of tree density and basal area: a case study on Scots Pine (Pinus silvestris L.) - Robiansyah, Iyan (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2011)
While quadrat shape of 10 x 10m has been commonly used in tree studies, the efficiency of this shape compared to the other shapes of size 100 m2 has not been tested. In this study, effect of various shapes of 100 m2 quadrat on measurement of Scots Pine (Pinus silvestris L.) density and basal area would be assessed. The aim was to assess the effect of quadrat shapes of 10 x 10m, 5 x 20m and 2 x 50m on the estimation of density and basal area of the pine in two woodlands in Norwich and to find the most efficient shape, statistically and with respect to sampling time. The results from all quadrat shapes similarly showed that the density and basal area of the Pines between two woodlands were significantly different. In site with lower pine density, the density and basal area measurement were not affected by variety of quadrat shapes. In site where the density of the Pine was higher, however, mean density and basal area measurement using 2x50m quadrat gave higher value than of the other two shapes. In term of efficiency, all shapes were not significantly different in statistical precision and sampling time. Shape of 5x20m, however, was more preferable as it required fewer samples before the mean of density and basal area always falls inside the 95% confidence interval of whole samples mean.